2004
DOI: 10.1179/acb.2004.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Features of 14 Non-Hodgkinʼs Lymphomas Associated With Coeliac Disease

Abstract: Lymphomas associated with coeliac disease are heterogeneous and their diagnosis is difficult. The enteropathy-associated T-cell lymphoma is the most frequent, aggressive and fatal complication of coeliac disease but it is not rare to observe association with B-cell lymphoma. Chemotherapy is highly toxic in those patients. Despite a poor prognosis, long-term survival can be expected in a fraction of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…The rising incidence of EATL is concerning, particularly in light of the poor survival. We found a median survival of 6 months, which is consistent with the existing literature, which shows a range of median survival of 5–12 months (4,5,7,19,20,22,24,28,30). Strikingly, we found that year of diagnosis did not affect survival, indicating that outcomes in EATL have not improved over the past 2 decades.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rising incidence of EATL is concerning, particularly in light of the poor survival. We found a median survival of 6 months, which is consistent with the existing literature, which shows a range of median survival of 5–12 months (4,5,7,19,20,22,24,28,30). Strikingly, we found that year of diagnosis did not affect survival, indicating that outcomes in EATL have not improved over the past 2 decades.…”
Section: Discussionsupporting
confidence: 91%
“…EATL and celiac disease are closely connected, with celiac disease being found in 38%-100% of those with EATL (4,24,26). Celiac disease can be diagnosed months to years before EATL or diagnosed simultaneously (2,(26)(27)(28). Most commonly, EATL develops in roughly 50% of those with refractory celiac disease type II, and this process is believed to be driven by activating mutations in the JAK/STAT pathway leading to dysregulated cytokine signaling and a fundamental role of interleukin-15 (23,26,(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…As the presence of enhanced levels of CIC in this work was especially found in patients with NHL, and was also reported in other publications [19], it seems that in people where antibody immunoreactivity is present in the form of immune complexes could be an enhanced immune stimulation elicited by these CIC. Data on the immunoreactivity to gliadin antigens are in accordance with well known association of gluten intolerance and NHL [13,20]. It is especially important to note that in this work, the immunoreactivity with gliadin is found to be present in patients with B cell type NHL, mostly in diffuse large B cell NHL as this type in this study was the most common one, which are along with the data of Smedby et al [21], in the presence of celiac disease in patients with mentioned type of NHL.…”
Section: Discussionsupporting
confidence: 82%
“…Strictly, Burkkit's lymphoma is found to be associated with Epstein Barr virus, MALT lymphoma with Helicobacter pylori, while primary effusion lymphoma was found to be associated with human herpes virus type 8 [1,6]. From the other side, the association of some of autoimmune diseases such as lupus, psoriasis, Sjögren's syndrome, with NHL, is also well documented in recent papers [7][8][9][10][11][12][13]. The association of celiac disease is also reported in diffuse large B cell NHL as well as in enteropathy-associated T cell NHL [12,13].…”
Section: Introductionmentioning
confidence: 83%
“…Case series of patients with NHL associated with CD have yielded variable results but suggested that selected patients may enjoy prolonged survival. 148,151,152,169,170 One study suggested that the prognosis of stage IV NHL was worse in patients with CD compared with those without CD. 169 Therapy of ETL is currently unsatisfactory, with a 5-year survival ranging from 11% to 20% in 2 studies and a 2-year survival of 28% according to another study.…”
Section: Lymphomamentioning
confidence: 99%